Czynniki wpływające na postawy młodych ludzi wobec prokreacji - Owsiejczyk, Aurelia (Wydawnictwo Naukowe UAM, 2008)
The author of the article attempts to characterise various factors that influence procreation among young people. Changes in the attitudes towards procreation, both for and against generating offspring, are best seen in the group under discussion. Young, educated people are open to new opportunities, development paths, and trends. It is up to these people and to their offspring what the future Polish society will look like.
Factors that influence young people's attitudes towards procreation